Expanding the area of distribution of Eufriesea fragrocara Kimsey (Hymenoptera, Apidae) in the Brazilian Amazon Forest - M. H. S. Souza; T. J. Izzo; E. J. Anjos-Silva (Scientific Electronic Archives, 2014)
The expansion of agriculture in the Arc of Deforestation causes deforestation and habitat loss. Euglossines sampling was done near Juruena River, Cotriguaçu municipality, northern Mato Grosso State. The bees were collected on understory and canopy using different baits. A total of 41 males of Eufriesea fragrocara Kimsey were collected. This is a rare species in collections and catalogued only in Huánuco (Peru), Napo (Ecuador), Ouro Preto D’Oeste and Ariquemes, Rondônia, Brazil. This new records increase the geographic distribution of E. fragrocara in 500 km to the western Amazon Basin, reducing the filling gaps in their distribution range in the Neotropics.